(untitled) (Bangladesh Journal of Animal Science, 2015)
An experiment was conducted with 160, day old Cobb 500 broiler chicks to evaluate the effect of supplementation of Grow Power (GP) on the performance of broiler. The dietary treatments were control (D1), Grow Power (D2), Grow Power plus antibiotic (D3) and antibiotic (D4). At 5th week of age, the body weight of birds at different dietary treatments were 938.75, 1105.00, 1136.25, and 985.00g in the diets of D1, D2, D3 and D4, respectively. Body weight gain at 2nd, 3rd and 4th week of age were significantly (P<0.05) higher in GP supplemented group (D2) and GP plus antibiotic group (D3) than that of control (D1) and antibiotic (D4) groups. Feed consumption during the experimental period was 1753.75, 1938.75, 1917.50 and 1774.50g for D1, D2, D3 and D4, respectively. At 2nd and 3rd week of age, feed consumption were significantly (p<0.05) higher in D3 group than the other groups including control. Significantly (P<0.05) better Feed Conversion Ratio (FCR) was found in D3 (2.03) and D2 (2.11) groups compared to D1 (2.31) and D4 (2.28). At 3rd, 4th and 5th week of age, the Performance Index (%) was significantly higher in D2 than D1 and D4. Meat yield parameter of broilers showed significant (P<0.05) differences in dressing weight, feather weight, shank weight, drumstick weight, neck weight, liver weight and viscera weight. Based on the results obtained from the current study it may be concluded that the inclusion of Grow Power @ 50gm/100kg of mixed feed with or without antibiotic improved the growth of commercial broiler including their FCR and therefore, this product may be considered as an alternative of traditional antibiotic in broiler diet. DOI: http://dx.doi.org/10.3329/bjas.v44i1.23139 Bang. J. Anim. Sci. 2014. 44 (1): 33-39